Bacterial Biofilm Probed by Scanning Electrochemical Microscopy: A Review. Issue 19 (5th October 2022) - Zhou, Yan; Zhang, Junjie; Zhao, Yuxiang; Liu, Yulin; Li, Fei
Abstract: Bacterial biofilm, a highly structured community with developmental processes from cell adherence to highly dense biofilms, is of critical concern in many industries. Investigations of parameters mediating biofilm formation, interactions between bacterial species, and parameters governing biofilm stability are quite important for understanding mechanism of biofilm formation. Scanning electrochemical microscopy (SECM), a local electrochemical technique using a microelectrode as its probe, can monitor microbe interactions in situ via detection of small molecules or biochemical cues with spatial and temporal resolution. In this review, we summarize the recent advances in biofilm research using SECM. First, we introduce the applications and potential biochemical cues of biofilms. Then, we classify the applications based on the bacterial species of interest, focusing on SECM to study key biochemical cues and highlighting underlying metabolic processes involved in biofilm formation. Finally, we discuss the challenges and limitations given the complexity and diversity of biofilms for future SECM studies. Abstract : SECM for bacterial biofilms studies : This review article introduces state‐of‐the‐art applications of scanning electrochemical microscopy (SECM) in bacterial biofilm studies, by summarizing the relevant biochemical cues that can be detected using SECM and highlighting the specific bacterial species as well as their corresponding applications.